An overview of unresolved issues in the perioperative management of liver transplant patients - Saurabh Mittal; Medha Bhardwaj; Praveenkumar Shekhrajka; Vipin Kumar Goyal; Ganesh Ramaji Nimje; Sakshi Kanoji; Suma Katyaeni Danduri; Anshul Vishnoi (Korean Journal of Transplantation, 2023)
Over the past decade, the field of solid organ transplantation has undergone significant changes, with some of the most notable advancements occurring in liver transplantation. Recent years have seen substantial progress in preoperative patient optimization protocols, anesthesia monitoring, coagulation management, and fluid management, among other areas. These improvements have led to excellent perioperative outcomes for all surgical patients, including those undergoing liver transplantation. In the last few decades, there have been numerous publications in the field of liver transplantation, but controversies related to perioperative management of liver transplant recipients persist. In this review article, we address the unresolved issues surrounding the anesthetic management of patients scheduled for liver transplantation.